MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA KONKRET LAPBOOK PADA MATA PELAJARAN BAHASA INDONESIA KELAS II SD NEGERI 01 NAMBANGAN KIDUL - Rahayu Ning Tyas; Fauzatul Ma’rufah Rohmanurmeta; Fuji Lestari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This classroom action research aims to improve students' learning outcomes and critical thinking skills through the implementation of the Problem Based Learning (PBL) model assisted by concrete lapbook media. The study was conducted in Grade II at SDN 01 Nambangan Kidul using a mixed-methods approach. The results showed a significant increase in student engagement and learning outcomes, as evidenced by evaluation and observation data. Student activity reached 72.37% and teacher activity 76.14%, with 83.33% of students achieving learning mastery, while three students did not meet the criteria. Following improvements in the subsequent stage, student activity rose to 90.79% and teacher activity to 94.32%, with all students achieving complete mastery. The PBL model supported by lapbook media has proven effective in enhancing students' critical thinking skills and environmental awareness.